Typology of popular scientific periodicals in the early 20th century - Yu.B. Balashova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The national system of popular scientific periodicals in Russia developed during the early 20th century as part of various educational initiatives. Under the conditions of insufficient amount of knowledge about the history of this important segment of Russian periodicals, it seems urgent to elaborate a typological approach to its research. The paper highlights and briefly describes the main typological groups of Russian popular scientific periodicals in the early 20th century. The following main groups of popular scientific journals of the studied period have been considered: highly specialized (monothematic), universal, mass-educating and entertaining editions. It has been concluded that the model of popular scientific periodicals in the early 20th century combined the functions of enlightenment, education, and entertainment. The emphasis on the union of sciences, self-education of the audience, fascination, and rich set of illustrations was retained even under the conditions of radical changes of the Soviet sociopolitical paradigm. The existing principles of scientific education proved to be so effective that they remained in effect until the World War II.